A Comparative Study of Nursing Services Between MPKP and Non-MPKP Hospital in Tangerang - Ibnu Hajar; Muhamad Hadi; Eni Widiastuti; Harif Fadhilah; Nyimas Heny Purwati; Satinah Satinah (UIMA Press, 2023)
Background: Health services are increasingly competitive so that they carry out various development actions in the industrial era 5.0. Nursing is one that provides services. The services provided must meet predetermined service standards so as to achieve service quality which has an impact on patient satisfaction. There are various assignment methods in nursing services with their advantages and disadvantages and their use is adjusted to the characteristics of each institution. Objectives: To compare whether there is an average difference in patient satisfaction with the MPKP method with non MPKP. Methods: Research design descriptive analytic comparative study through surveys. The total number of samples is 60 respondents. Analysis using the T test Independent Test. Results: The average patient satisfaction with the MPKP method is better than the non-MPKP method. Statistical test results on the dimensions of satisfaction; reliability with P value = 0.000, assurance with P value = 0.004, tangibles with P value = 0.000, empathy with P value = 0.000 and responsiveness with P value = 0.000. So that the P value <0.05, which means that there is a significant positive difference in the average patient satisfaction in the dimensions of reliability, assurance, tangibles, empathy and responsiveness between the MPKP method and non-MPKP methods. Conclusion: There is a significant difference in the average patient satisfaction in the MPKP method with non-MPKP methods Keywords: Comparative, Nursing, PNPM, RATER, Team